PENGUATAN DEMOKRASI DAN PARTISIPASI WARGA NEGARA DALAM MENGEMBANGKAN EKONOMI KREATIF DI DESA SEKITAR MA’HAD AL-ZAYTUN, INDRAMAYU - Rahim, Abdur; Setiawan, Rizal Ahmaludin; Marjuki, Ali; Wasikin, Wasikin; Jumanta, Toto; Hizbullah, Diva; Gumilang, Ibnu Fajar; Ikhwanudin, Muhammad; Nursabilah Isu, Mutimah; Fatma, Azwar Ayu; Fitri, Anisa; Putri, Amelia Fajri (Jurnal Abdimas Bina Bangsa, 2025)
Village development is an integral part of national development aimed at improving community welfare equitably. Democracy in the context of village development is a crucial aspect, considering that citizen participation in decision-making processes can drive more inclusive and needs-oriented policies. The creative economy is an economic sector based on creativity, innovation, and the utilization of culture as its primary resource. The villages surrounding Ma’had Al-Zaytun have various creative economic potentials, such as handicrafts, regional culinary specialties, and traditional performing arts. The goal of this Community Service activity is to strengthen democracy and citizen participation in developing the creative economy in the villages around Ma’had Al-Zaytun, Indramayu. Results of the Community Service Program is the implemented program has had a positive impact on strengthening democracy and developing the creative economy in the villages around Ma’had Al-Zaytun, Indramayu. In terms of democracy, there has been a significant increase in the level of citizen participation in village decision-making processes. Training and mentoring programs have successfully raised awareness among residents about the importance of their involvement in village deliberations and other development activities. Before the program was implemented, the level of citizen participation in village forums was only around 30%, but it increased to 65% after the intervention. Regarding the creative economy, the number of creativity-based businesses has increased by 40% over the past two years. Various creative economy sectors, such as handicrafts, regional culinary specialties, and performing arts, have experienced rapid growth thanks to training in product innovation and marketing strategies. Additionally, collaboration between residents, village governments, academics, and the private sector has strengthened the creative economy ecosystem in the villages. The benefits gained by village residents from this program include increased political and economic literacy, the growth of new business opportunities, and expanded market access through digital platforms and local product exhibitions. Thus, this program not only enhances the economic well-being of residents but also reinforces the sustainability of village development in a participatory and inclusive manner.